Dispensasi Kawin di Pengadilan Agama Soasio: Antara Regulasi dan Kemaslahatan bagi Anak - Berliana Dyah Cahyo Wati Putri; Marwa, Muhammad Habibi Miftakhul (Universitas Muhammadiyah Yogyakarta, 2025)
Marriage dispensation is a policy of granting rights to men and 19 years of age. Marriage dispensation has become a phenomenon and a serious concern because the number of applications for marriage dispensation continues to increase among teenagers. One of the main factors driving the application for marriage dispensation is pregnancy outside of marriage. The purpose of this study is to analyze in depth the application of the best interests of children in granting marriage dispensation at the Soasio Religious Court based on the theory of welfare. This study was written using a type of normative juridical legal research because it uses secondary data obtained through literature studies. The results of this study indicate that there are four marriage dispensation regulation regimes in Indonesia, namely the regime before the Marriage Law, the Marriage Law regime, the Constitutional Court Decision Number 22/PUU-XV/2017 regime, and the Amendment to the Marriage Law regime. The Soasio Religious Court applies the principle of the best interests of children in granting marriage dispensation referring to the protection of children's rights. Marriage dispensation will be granted or approved by the Soasio Religious Court if it is considered to provide benefits to individuals, families, and society. If the granting of marriage dispensation actually causes harm, then the application for dispensation is worthy of being rejected or not granted